Corporate Governance Mechanisms and Sustainability Reporting Practices of Listed Non-Financial Firms in Nigeria - Razaq, Abubakar Garba; Alhassan, Abdulkarim; Omole, Paul Martins (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The Board plays a pivotal role in the administration of corporate affairs. An effective Board oversight function basically consists of proper mechanisms for providing entrepreneurial and strategic leadership as well as promoting ethical values that allow stakeholders to exercise their rights to protect their investments’ sustainability. This study examined the effect of corporate governance mechanisms on sustainability reporting of listed non-financial firms in Nigeria. The study measured corporate governance attributes with board size, board independence, board gender diversity, board financial expertise and sustainability reporting was measured by sustainability disclosures metrics in line with Global Reporting Initiative (GRI) standards. The study adopted correlation research design relying on secondary data obtained from annual reports of the population, which comprised of 116 non-financial firms listed on Nigeria Exchange Group (NGX) as at 31st December 2020 with a sample size of 51 firms, covering the period of 2011 – 2020. The study employed multiple regression panel model to analyze the data with the aid of E-view 10 statistical tool. According to the results of random effect regression, board size and board members’ financial expertise have positive and significant effect on sustainability reporting. Based on the findings, the study concluded that corporate governance attributes have the capacity to effectively enhance the sustainability reporting of firms. Thus, the study recommended among others that regulators in financial reporting should mandate firms to have a sizeable board with members having financial expertise as a measure of enhancing sustainability reporting in Nigeria.